Maria, modelo e mãe da Igreja: um estudo sobre a reforma litúrgica mariana do Concílio Vaticano II, à luz da Exortação Apostólica Marialis Cultus, de Paulo VI, em interface com a inteligência senciente, de Xavier Zubiri - Toledo, Bruno Rodrigues (2024)
Reflecting or researching the figure of Mary Most Holy, as Mother of God and model of the Church, seems to be a redundancy and or that we could run the risk of “rain in the wet” in the face of everything that has already been said on this topic. However, we can see that there are no limits when we are faced with a source of divine graces such as the life of Mary. From a formal point of view, we ask: what else will it be possible to reflect on Mary, Mother of God and of the Church today? It is a bibliographic research, whose expected results are limited to the understanding and faith that the more we dedicate ourselves to studies on the figure of Mary, Mother of God and of the Church, the more we nourish ourselves with her grace and the more the Church itself becomes strengthens. With the interface of Xavier Zubiri's sentient intelligence combined with Paul VI's Mariology, both being distinct concepts within their respective philosophical and theological domains, they can be examined in terms of their convergence in relation to the valorization of the experiential and affective dimension of humanity